In vivo measurement of skin erythema and pigmentation: new means of implementation of diffuse reflectance spectroscopy with a commercial instrument - Stamatas, G.N.; Zmudzka, B.Z.; Kollias, N.; Beer, J.Z. (British journal of dermatology (1951), 2008)
Summary Background  Various physical, chemical and biological insults, including exposure to ultraviolet (UV) radiation, cause erythema and change in pigmentation in human skin. These reactions provide an important measure of the cutaneous response to the insult. Objectives  To present a new implementation of a method for objective in vivo measurement of erythema and pigmentation. Methods  The method is based on acquisition of reflectance spectra in the visible range using a commercially available spectrophotometer. The probe of this instrument incorporates an integrating sphere that captures the light remitted from the skin in a wide range of angles. We corrected the acquired reflectance spectra for the contribution of specular reflections by an amount given by the Fresnel equation and verified this correction experimentally. This correction is particularly important when measurements are performed on heavily pigmented skin. The corrected reflectance spectra are then transformed into absorbance spectra. To analyse these spectra, we developed an algorithm which can be used to calculate apparent concentrations of oxyhaemoglobin, deoxyhaemoglobin and melanin. This method was tested in clinical studies of skin reactions induced by exposure to UV radiation. These experiments involved three groups of subjects with progressively darker complexion (constitutive pigmentation). Each group consisted of 10 subjects. Erythema was measured 1 day after UV exposure, and pigmentation (melanin content) 1 week later. Results  Distinct apparent absorbance spectra were obtained for dark, intermediate and fair skin. There was good agreement between reconstructed spectra and experimental data at relevant wavelengths. Difference absorption spectra were able to show the dose dependence of UV‐induced responses, and erythema and pigmentation values obtained by the spectroscopic method showed good correlation with those derived by subjective visual grading. Conclusions  The results demonstrate that the presented methodology provides an objective noninvasive way of measuring UV‐induced reactions independently of the level of constitutive pigmentation.